Peran komitmen organisasi sebagai pemediasi hubungan antara kompensasi, motivasi, dan kinerja pegawai - Shania Ayanda Nur; Soni Harsono; Tjahjani Prawitowati (Journal of Business & Banking)
This study analyzes the role of organizational commitment as a mediator between compensation, motivation, and performance of PPNPN employees at the Pusdatin of the Ministry of ATR/BPN, with a sample of 48 employees using a saturated sampling technique. The role of PPNPN is important to study because it will be able to explain its contribution to the performance of government agencies because PPNPN performance is measured through plans and performance targets made by employees and must be achieved within a certain period of time or what is commonly referred to as Employee Performance Targets (SKP). Performance targets made at the beginning of the year will then be assessed at the end of the year and their compliance with the predetermined targets will be assessed. The analysis technique used is SEM-PLS with the WarpPLS 8.0 program, and data was collected through a Google Form questionnaire. The results of the study indicate that compensation does not have a significant effect on employee performance, while motivation and organizational commitment have a significant positive effect on performance. Organizational commitment also mediates the effect of compensation and motivation on employee performance. The implication of this study is the importance of programs to improve organizational commitment and PPNPN motivation in order to encourage employee performance.